2015
DOI: 10.1007/s13595-015-0474-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and tree responses in Central European forests

Abstract: Research on climate change effects concerns most ecosystems and species worldwide. There is strong evidence that forests in all parts of the world are affected by changing temperatures and aggravating drought situations (Allen et al. 2010). Marked range shifts of tree species are projected as a consequence of extensive and large climatic changes (Hanewinkel et al. 2013). In this frame, the International Conference on "Climate Change and Tree Responses in Central Europe" held in September 2013 in Zurich, Switze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Hence, a shift from conifer dominated forests towards forest with higher amounts of deciduous species is expected (Lindner et al 2010) as discussed in corresponding literature (e.g. Milad et al 2011;Spathelf et al 2014;Wohlgemuth 2015).…”
Section: Introductionmentioning
confidence: 72%
“…Hence, a shift from conifer dominated forests towards forest with higher amounts of deciduous species is expected (Lindner et al 2010) as discussed in corresponding literature (e.g. Milad et al 2011;Spathelf et al 2014;Wohlgemuth 2015).…”
Section: Introductionmentioning
confidence: 72%
“…Projections of climatic change have amplified the debate on whether tree species composition in European forests has to be actively managed in order to guarantee forest continuation, protection against natural hazards and economically important timber production in the coming century (Bussotti et al 2015;Lindner et al 2014;Wohlgemuth 2015). Foresters have long been studying non-native tree species that could enhance wood production under current climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no comparable study exists so far. However, impacts studies have shown the decisive role of climate for the future of tree species in Austria [ 61 ] and neighbouring countries [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%